Phytochemical, Antibacterial and Antifungal Activities of Alkaloids Extracted from Peganum harmala (Linn.) Seeds of South of Algeria - Behidj-Benyounes, N.; Dahmene, T.; Allouche, N.; Laddad, A. (Asian Journal of Chemistry, 2014)
This work reports the phytochemical screening of the plant extracts recovered from the seeds of Peganum harmala L. (Zygophyllaceae). Preliminary phytochemical analysis of plants extracts showed the presence of alkaloids, coumarins, saponins, quinones and flavonoids free. These natural substances are recovered by different solvents (aqueous, ethanolic and hexane). Thus evaluation of the antimicrobial activity has only touched the alkaloids. The antimicrobial effect of alkaloids is evaluated on several microorganisms. It should be noted that these agents are characterized by a high frequency of contamination and pathogenicity. It is noted that Staphylococcus aureus, Saccharomyces cerievisae and E. coli are very sensitive in respect of the ethanol extract. Pseudomonas aerogenosa and Penicillium sp. are resistant to this extract. The other microorganisms are moderately sensitive. The study of the antimicrobial activity of different extracts of the seeds of Peganum harmala L. showed an optimal activity with the ethanol extract.